Interpretative peculiarities and Peculiar Choices in Translating Goldoni's Comedies - Radoš-Perković, Katja (2010)
The translational choices in the example of Goldoni's comedies are justified most of the time by their efficiency and strong appeal to the public in the final product they were intended for, that is the stage production. Nevertheless, some of the gratest production hits such as „Ribarske svađe“ (Le baruffe chiozzotte) are based on slightly over-creative, sometimes also miss-interpretations of the original. In this study the examples are limited to the names and nicknames of characters.